Service included four-star secrets of an eavesdropping waiter - Damrosch, Phoebe 1978- (New York William Morrow, 2007)
Damrosch, former waiter at the New York City restaurant Per Se, details her career as a waiter, describing the intimate workings of restaurant table service at its best. Tales of critics and celebrities spice up the memoir with a few tips on how to earn a waiter's respect sprinkled throughout.
The art of the day job -- Food porn -- Mosquitoes on toast -- Fire! -- Four-star mistress -- Being frank -- No bones about it -- The fault, dear Bruni -- Not in the stars -- Underlings -- I can hear you -- City love -- Service included -- A few more tips -- Afterword: My dinner with André -- Per se menu.
HE-4612g, donated by Ms. Jowana B. Bueser.
Keywords: Damrosch, Phoebe -- 1978-.; Per Se (Restaurant); Waitresses -- United States -- Biography; Food service -- New York (State) -- New York -- Anecdotes